Importance of native vegetation for detection and management of rice stink bug (Tibraca limbativentris) - Fuentes Rodríguez, Daniela Alejandra (2020)
Tibraca limbativentris (Hemiptera: Pentatomidae) is a major pest in Neotropical rice agroecosystems. In autumn–winter, this pest takes refuge in rice stubble and in native vegetation, which allows it to re-colonize the crop during the rice growing season. However, it is still unknown whether this vegetation is a pest sink or is actually a natural trap that contributes to pest population biocontrol. Here we present information on the insect's alternative host plants, a preliminary outline of the relationship between plant phylogeny and insect abundance, and the impact that winter natural enemies have in pest population. Also, we include a proposed methodology for pest density analysis in winter hosts. Our results show significant differences in the abundance/density that T. limbativentris reaches in the 12 host plant species present in our study areas, with a plant-use pattern significantly related to the phylogenetic clade of Poales. Stink bug winter populations mainly comprised diapause adults, and 40% of insect digestive tracts had content. Survival of T. limbativentris was 56.92% in winter hosts. About mortality, 10% was due to undetermined causes and 33.08% due to entomopathogenic fungi, showing a natural regulation of the pest population. Our results suggest that native vegetation impacts winter survival of T. limbativentris. Although these plants offer shelter, they offer a greater contribution to Integrated Pest Management: the natural regulation of winter pest populations through entomopathogenic attack. Further studies on T. limbativentris population dynamics and the preservation of native areas near rice fields will be required for the development of best control practices.